Sotos syndrome - A Juneja; A Sultan (Wolters Kluwer Medknow Publications, 2011)
Sotos syndrome is a well-defined childhood overgrowth syndrome characterized by pre- and postnatal overgrowth, developmental delay, advanced bone age, and a typical facial gestalt including macrodolichocephaly with frontal bossing, frontoparietal sparseness of hair, apparent hypertelorism, downslanting palpebral fissures, and facial flushing. This report presents a case of Sotos syndrome in a 5½-year-old child.